A Faculdade Interamericana de Educação na expansão da pós-graduação no Brasil - Clovis Renan Jacques Guterres; Oswaldo Alonso Rays (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2005)
In this text we aimed at highlighting and commenting substanctive aspects of the first phase of the current Post- Graduation Program in Education from the Universidade Federal de Santa Maria, RS, originally from a multinational project developed in the form of a covenant between the Brazilian Government and the Organization of American States (OAS), in the period from 1970 to 1977. This project which is denominated as Faculdade Interamericana de Educação (Interamerican College of Education FIE) was the responsible by the implantation and development of one of the first Education Masters Program in the contryside of Brazil. For the brief understanding of its implications for the Post-Graduation espansion process in Brazil, we aimed at rebuilding its trajectory from the Cold War context, from the determinations of the OAS integration policy and the stricto sensu post-graduation expansion policy in Brazil.